2018
DOI: 10.1177/0748233718809256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coenzyme Q10 supplementation on oxidative stress and antioxidant enzyme activity in glazers with occupational cadmium exposure: A randomized, double-blind, placebo-controlled crossover clinical trial

Abstract: Recently, there is a growing interest for the use of antioxidants as a preventive agent against cadmium (Cd) intoxication. The current study aimed to investigate the effects of dietary coenzyme Q10 supplementation on oxidative stress and antioxidant enzymes activity in Cd-exposed glazers. In a randomized, double-blind, placebo-controlled 2-month crossover clinical trial, coenzyme Q10 (60 mg twice daily) or placebo was administrated to 40 male glazers occupationally exposed to Cd. The subjects were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The range of mean age among these participants was from 17.2 to 79.2 years. Five studies only contained male subjects in healthy status or special occupation [ 32 , 33 , 34 , 35 , 36 ]. Conversely, there were two studies conducted among women only [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of mean age among these participants was from 17.2 to 79.2 years. Five studies only contained male subjects in healthy status or special occupation [ 32 , 33 , 34 , 35 , 36 ]. Conversely, there were two studies conducted among women only [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taking CoQ10 for 8 weeks also significantly changed the levels of them except SOD. However, it is worthy to note there were only two RCTs that included evaluating the effect of 8-week CoQ10 supplementation on SOD levels [ 32 , 63 ]. Only three RCTs conducted CoQ10 intervention for more than 12 weeks [ 55 , 56 , 62 ]; hence we could not conclude that longer intervention time would bring about better antioxidant effects of CoQ10 yet.…”
Section: Discussionmentioning
confidence: 99%
“…MDA is the best product to evaluate lipid peroxidation ( Sepidarkish et al, 2020 ), and it has been shown that CoQ10 can prevent lipid peroxidation and reduce MDA in vitro and in vitro ( Talevi et al, 2013 ; Gholnari et al, 2018 ; Hormozi et al, 2019 ). CoQ10 supplementation may reduce MDA levels via several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that long-term occupational exposure to a low-level mixture of VOCs, including benzene, toluene, and xylene, is associated with decreased TAC levels in serum (Maksoud et al, 2018; Verma et al, 2017; Zhao et al, 2008). The serum TAC offers a complete panorama of the function of antioxidant system in the body under oxidative stress (Hormozi et al, 2018a). In the present study, although there was a small decrease in serum TAC levels of PWs compared to that of the control subjects, these effects were not statistically significant ( p =.088).…”
Section: Discussionmentioning
confidence: 99%